1971
DOI: 10.1172/jci106512
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal regulation of human lower esophageal sphincter competence: interaction of gastrin and secretin

Abstract: A BSTRACT The interaction of gastrin and secretin, in the regulation of human lower esophageal sphincter competence, was studied in 54 normal subjects. A doseresponse curve, for the lower esophageal sphincter, was constructed from the rapid intravenous injections of synthetic gastrin I (amino acid sequence 2-17). This curve was sigmoid shaped and showed a peak response that was 460.0 ±24.0% (mean ±2 SE) of the initial sphincter pressure, at a dose of 0.7 /g/kg of gastrin I. Secretin, either endogenously releas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
75
1
1

Year Published

1973
1973
1989
1989

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 205 publications
(80 citation statements)
references
References 18 publications
3
75
1
1
Order By: Relevance
“…The most likely mechanism by which the pylorus serves this protective function would be the release of the duodenal hormones, secretin and cholecystokinin, in response to acidification. This would be analogous to the role of gastrin in maintaining lower esophageal sphincter competence (12)(13)(14). However, other hormonal or neural pathways can not be excluded.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The most likely mechanism by which the pylorus serves this protective function would be the release of the duodenal hormones, secretin and cholecystokinin, in response to acidification. This would be analogous to the role of gastrin in maintaining lower esophageal sphincter competence (12)(13)(14). However, other hormonal or neural pathways can not be excluded.…”
Section: Discussionmentioning
confidence: 99%
“…The lower esophageal sphincter contracts in response to gastrin (12)(13)(14) whereas both the ileocecal (15) and choledochal sphincters (16) (25) and suggested that contaminants present in the GIH Research Unit preparation of cholecystokinin were not solely responsible for the observed response (26)(27)(28).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concerning the relationship between the rise in serum gastrin and LESP, exogenous gastrin such as gastrin 17 is capable to increase LESP but only in a pharmacologic dose (Cohen and Lipshutz 1971). Recently, it was reported, however, that gastrin 17 when administered in physiologic doses failed to increase LESP (Freeland et al 1976 ;Jennewein et al 1976).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, there has been considerable investigation into the function of the esophagus and the lower esophageal sphincter (LES) ' in man and in animal models (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11). These studies have described multiple mechanisms by which the esophagus and the LES responded to the various demands placed upon it.…”
Section: Introductionmentioning
confidence: 99%